Extended Working Life Policies International Gender and Health Perspectives - Ní Léime, Áine; Ogg, Jim; Rašticová, Martina; Street, Debra; Krekula, Clary; Bédiová, Monika; Madero-Cabib, Ignacio (Springer Nature, 2020)
This open access book addresses the current debate on extended working life policy by considering the influence of gender and health on the experiences of older workers. Bringing together an international team of scholars, it tackles issues as gender, health status and job/ occupational characteristics that structure the capacity and outcomes associated with working longer. The volume starts with an overview of the empirical and policy literature; continues with a discussion of the relevant theoretical perspectives; includes a section on available data and indicators; followed by 25 very concise and unique country reports that highlight the main extended working life (EWL) research findings and policy trajectories at the national level. It identifies future directions for research and addresses issues associated with effective policy-making. This volume fills an important gap in the knowledge of the consequences of EWL and it will be an invaluable source for both researchers and policy makers.